2013
DOI: 10.1089/end.2012.0605
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Comparison of the Safety and Effectiveness of Ureteroscopic Laser Lithotripsy in Obese and Normal Weight Patients

Abstract: SFRs using ureteroscopic lithotripsy in obese and overweight populations are the same as in the normal weight patients. A flexible ureteroscope was associated with a decreased SFR, but this likely due to a more proximal stone location in these patients. Ureteroscopic laser lithotripsy is an effective and safe technique to treat urolithiasis in the overweight/obese patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Hypothetically, the placement of a UAS during ureteroscopy can circumvent issues of visibility related to body habitus. However, Chew et al [ 11 ] concluded that ureteroscopy for obese patients are equally efficacious when compared to non-obese patients, and their data showed that UAS placement in obese patients did not affect SFRs. Their study results are consistent in the notion that external obesity does not necessarily correlate with an aberrant internal anatomy; factors such as increased retroperitoneal fat in obese patients do not influence the ability of the urologist in gaining access with a flexible ureteroscopy, with or without an UAS.…”
Section: Does Uas Placement Always Improve Stone-free Rates?mentioning
confidence: 99%
“…Hypothetically, the placement of a UAS during ureteroscopy can circumvent issues of visibility related to body habitus. However, Chew et al [ 11 ] concluded that ureteroscopy for obese patients are equally efficacious when compared to non-obese patients, and their data showed that UAS placement in obese patients did not affect SFRs. Their study results are consistent in the notion that external obesity does not necessarily correlate with an aberrant internal anatomy; factors such as increased retroperitoneal fat in obese patients do not influence the ability of the urologist in gaining access with a flexible ureteroscopy, with or without an UAS.…”
Section: Does Uas Placement Always Improve Stone-free Rates?mentioning
confidence: 99%
“…The efficiency of fURS for obese and morbidly obese patients has been evaluated in various studies, and SFR and complication rates were found to be not affected by body mass index. [27][28][29] …”
Section: Rirs In Anticoagulated Patientsmentioning
confidence: 99%
“…The success rate of SWL is decreased with obesity and greater skin-stone distance, while PCNL becomes more complicated in obese patients due to the longer tracts and increased risk of anesthetic complications associated with prone positioning. The efficacy of fURS in the treatment of upper tract stones in obese and morbidly obese patients has been well studied [80] , [81] , [82] , [83] , [84] , [85] , [86] , and the SFR and associated complications of fURS were not affected by the patient's body mass index [84] , [85] , [86] .…”
Section: Stones In Special Situationsmentioning
confidence: 99%